WASP: Workload Agent-Based Simulation Platform for Migration Recommendations in Federated Kubernetes Environments - Cunha, Andre; Lima, Jose; Sampaio, Lilia; Farias, Giovanni; Morais, Fabio (Anais Estendidos do Simpósio Brasileiro de Redes de Computadores e Sistemas Distribuídos (SBRC), 2026)
Workload migration in federated Kubernetes environments is a complex task that requires well-defined migration strategies capable of operating under dynamic system conditions and constraints to balance performance, cost, and availability. However, enforcing them directly in production may lead to performance degradation, particularly under unvalidated autonomous agent-based operation. This paper presents WASP (Workload Agent-Based Simulation Platform), a decision-support tool that enables operators to simulate agent-based migration strategies before production deployment. WASP adopts a modular architecture with monitoring, recommendation, and execution control layers, supporting configurable policies with human-in-the-loop approval.